The novel MAGL inhibitor MJN110 enhances responding to reward-predictive incentive cues by activation of CB1 receptors. (1st January 2020) - Feja, Malte; Leigh, Martin P.K.; Baindur, Ajay N.; McGraw, Justin J.; Wakabayashi, Ken T.; Cravatt, Benjamin F.; Bass, Caroline E.
Abstract: CB1 receptor antagonists disrupt operant responding for food and drug reinforcers, and cue-induced reinstatement of cocaine and heroin seeking. Conversely, enhancing endocannabinoid signaling, particularly 2-arachidonyl glycerol (2-AG), by inhibition of monoacyl glycerol lipase (MAGL), may facilitate some aspects of reward seeking. To determine how endocannabinoid signaling affects responding to reward-predictive cues, we employed an operant task that allows us to parse the incentive motivational properties of cues. Rats were required to nosepoke during an intermittent audiovisual incentive cue (IC) to obtain a 10% sucrose reward. The CB1 receptor antagonist, rimonabant, dose-dependently decreased the response ratio (rewarded ICs/total presented) and active nosepokes per IC, while it increased the latency to respond to the cue and obtain the reward, indicating an overall decrease in both the choice and vigor of responding. Yet rats persisted in entering the reward cup. Using a modified version of the task, the novel MAGL inhibitor MJN110 increased the response ratio, decreased the latencies to respond to the IC and enhanced active nosepokes per IC, indicating a facilitation of cue-induced reward seeking. These effects were blocked by a subthreshold dose of rimonabant. Finally, MJN110 did not alter consumption of freely available sucrose within volumes obtained in the operant task. Together these data demonstrate blocking endocannabinoid tone at the CB1 receptor attenuates the ability of cues to induce reward seeking, while some aspects of motivation for the reward are retained. Conversely, enhancing 2-AG signaling at CB1 receptors facilitates IC responding and increases the motivational properties of the IC. Highlights: Rats were tested in an operant task that allows parsing motivation for incentive cues from other aspects of operant responding. Rimonabant dose-dependently reduced responding to reward-predictive incentive cues. MJN110 increased incentive cue responding by activation of CB1 receptors. CB1 receptor antagonism preferentially decreases motivation for incentive cues. Enhancing 2-AG signaling increases motivation for both the cue and the reward.